Analysis of Business Opportunities in Increasing The Income of MSMEs Actors at The Perumnas Karawang Morning Market - Afryani, Diah Kartika; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
This research is a study of the Analysis of Business Opportunities in Increasing the Income of MSME Actors in the Perumnas Karawang Morning Market. This research aims to find out how the income of MSME actors is in their initial place of selling, as well as to find out how business opportunities can increase the income of MSME actors at the Perumnas Karawang morning market. The method used in this research is descriptive qualitative. The research respondents were 30 MSMEs, consisting of 24 MSMEs who had businesses elsewhere, and 6 MSMEs who did not have their initial businesses locally. The 30 respondents selected were due to the large number of the same type of business in the Perumnas morning market. The research results showed that 30 respondents stated that business opportunities at the Perumnas morning market could increase income. This business opportunity provides additional income for all respondents. For example, MSMEs wholesalers of household equipment initially earned income of around IDR 12,7500,000, then increased to IDR 30,500,000 at the Perumnas morning market. April coincides with the month of Ramadan, providing an increase in income of up to 79.2% and December is also a moment when MSME players can get an increase in income of up to 63.6%. December coincides with the end of the year where many people get year-end bonuses. Apart from April and December, the percentage increase in income was relatively stable at 55%. This shows that business opportunities in the Perumnas morning market really provide opportunities for MSME actors to be able to increase their income